Rural Development Lessons: Institutional Insights on Good Corporate Governance in Village Owned Enterprises - Dyah Ayu Nur Safitri; Esa Septian; Sri Kasiami (Univiversitas Dr. Djar Wattiheluw, 2025)
This study examines the institutional dimensions of BUMDes Berkaho in implementing Good Corporate Governance (GCG) through the lens of institutional theory, employing a qualitative case study approach. The findings reveal that BUMDes Berkaho integrates GCG principles through responsive and innovative leadership, fostering transparency, accountability, and responsibility. Its operations are structured around legal frameworks, a clearly defined vision and mission, and organizational bylaws. Financial resources, infrastructure, and technology are managed effectively with government support, ensuring alignment between development programs, community needs, and local economic potential. A well- structured internal governance system further enhances transparency and accountability, underscoring the relevance of institutional theory in strengthening BUMDes as a catalyst for sustainable local economic growth.